Nature-Positive Solutions initiative baseline evaluation survey report: Kenya - Boukaka, Sedi Anne; Azzarri, Carlo; Davis, Kristin E.; De Falcis, Eleonora (International Food Policy Research Institute, 2024)
Conventional agriculture, while providing mass-scale production of cheap and plentiful food, has extracted a massive toll on both the environment and humans. On the one hand, industrial agriculture drives 80 percent of deforestation, threatens 86 percent of the 28,000 species currently at risk of extinction (through habitat conversion and pollution), is responsible for significant loss of crop and genetic diversity and up to 37 percent of global greenhouse gas emissions (GHGE), accelerates land degradation and land-use change, and uses 70 percent of global water resources withdrawn. On the other hand, it has reduced nutrition outcomes for families and farming incomes due to impoverished soil and water health, reduced crop resistance to pests and diseases, and poor waste management. This unsustainable food production toll is further exacerbated by misaligned public policies and economic incentives. There is an urgent need to shift to more resilient farming systems capable of supporting smallholder farmers and ensuring that agriculture is a net positive contributor to nature. In 2021 the United Nations Food Systems Summit formally recognized nature-positive production as one of five critical pathways to sustainable food systems (Von Braun et al. 2023).